Covid-19: disruptions in supply chain and credit markets: a brazilian empirical view - Almeida, Carlos Eduardo de (2023)
The first chapter introduces a novel methodology to map firm-level connections using payment data, providing a more detailed understanding of firm positions in the supply chain compared to traditional methods. The study analyzes over 370 million payment observations from Brazilian firms across all economic activities, leveraging the heterogeneity of COVID-19’s impact between capital cities and inland municipalities to uncover the consequences. The findings highlight the vulnerability of upstream firms to disruptions, a heterogeneous impact across economic activities and underscores firm adaptability. The study has implications for public policy discussions in industrial policy design and modeling financial frictions. The second chapter examines the reallocation of credit from capital-located clients to less risky inland clients by banks across Brazilian municipalities in response to COVID-19. The study investigates bank characteristics associated with a more pronounced credit reallocation, finding a reallocation toward clients in inland cities. Inland cities with highly concentrated local credit markets and lower outstanding credit had a more pronounced credit shift. The results indicate that the bank financing channel did not mitigate the effects of COVID-19 and may have become a pro-cyclical component.